HAK KONSTITUSIONAL PESERTA DIDIK DALAM PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Achmad Muchsin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This research is focused on students’ constitutional rights as consumers of education services in the perspective of consumer protection law. Using legislation and case-based approach, this research has uncovered, that the rights of learners related to the process of acceptance, fulfillment, and freedom of association. The admission process should be carried out at all levels, from the lowest to doctoral programs. Fulfillment of rights includes material and non-material. While its organizational freedom refers to the Higher Education Act.